2019
DOI: 10.1016/j.xkme.2019.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Bloodstream Infections in Hospitalized Hemodialysis Patients

Abstract: Resistance to at least 1 antimicrobial in 3 or more antimicrobial categories, which included extended-spectrum cephalosporins, fluoroquinolones, aminoglycosides, meropenem (all organisms); and piperacillin/tazobactam (Enterobacteriaceae and Pseudomonas aeruginosa). Denominators represent number of isolates tested to all antimicrobials/classes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…The United States Renal Data System (USRDS) in its 2020 data report revealed that, while adjusted rates of hospitalization for cardiovascular and other causes decreased over time, the rate of infection-related hospitalizations remained relatively unchanged between 2009 and 2018 2 . Furthermore, it has been found that the rates of bloodstream infections (BSIs), the most common infections among hemodialysis patients, have increased by 40% between 2003 and 2014 5 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The United States Renal Data System (USRDS) in its 2020 data report revealed that, while adjusted rates of hospitalization for cardiovascular and other causes decreased over time, the rate of infection-related hospitalizations remained relatively unchanged between 2009 and 2018 2 . Furthermore, it has been found that the rates of bloodstream infections (BSIs), the most common infections among hemodialysis patients, have increased by 40% between 2003 and 2014 5 .…”
Section: Discussionmentioning
confidence: 99%
“…While gram-positive cocci preponderate as a cause of BSI in hemodialysis patients, recently the proportion of BSIs caused by gram-negative pathogens is increasing, with one study showing a statistically significant increase in gram-negative pathogens and a decrease in Staphylococcus aureus causing BSIs over a 9-year period 5 . Another study showed that a quarter of BSIs were due to gram-negative pathogens resistant to common antimicrobials, with 25% of these isolates only sensitive to colistin 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation